Students Lived Experience on The Toughest Place to be a Binman in Critical Listening and Speaking 1 Class - Martha Pritzanda Pudhika (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2016)
The use of authentic videos has been implemented in Critical Listening and Speaking 1 (CLS 1) class. For instance, the use of The Toughest Place to be a Binman video. This video gives the students meaningful experiences. The students do not only get the material but they can also get social and environment issues that appear in the video. After watching the video, the students are expected to have their own experience towards the use of The Toughest Place to be a Binman video in CLS 1. Therefore, the aim of this research was to have a better understanding on the students lived experience on The Toughest Place to be a Binman in CLS 1. This research employed phenomenology study because this research focused on the students lived experience. As a research result, the research showed the participants stories and the interpretation. There were four emerging themes that appeared from the data processed. Those were meaningfulness, compassion, motivation, and action. Those four themes connected between each other.DOI: https://doi.org/10.24071/llt.2016.190206